Investigations Exploring the Use of an Unstructured-Grid, Finite-Volume Modelling Approach to Simulate Coastal Circulation in Remote Island Settings—Case Study Region, Vanuatu/New Caledonia - Lee, Serena Blyth; Zhang, Fan; Lemckert, Charles James; Tomlinson, Rodger (Frontiers in Marine Science, 2021)
Understanding coastal circulation and how it may alter in the future is important in island settings, especially in the South West Pacific, where communities rely heavily upon marine resources, and where sea level rise (SLR) is higher than the global average. In this study we explore the use of an unstructured-mesh finite-volume modelling approach to assist in filling the knowledge gaps with respect to coastal circulation in remote island locations—selecting the Vanuatu and New Caledonia archipelagos as our example study site. Past limited observations and modelling studies are leveraged to construct and verify a regional/coastal ocean model based on the Finite-Volume Community Ocean Model (FVCOM). Following verification with respect to tidal behaviour, we investigate how changes in wind speed and direction, and SLR, alter coastal water levels and coastal currents. Results showed tidal residual circulation was typically associated with flow separation at headlands and islands. Trade winds had negligible effect on water levels at the coast, however, wind-residual circulation was sensitive to both wind speed and direction. Wind-residual currents were typically strongest close to coastlines. Wind residual circulation patterns were strongly influenced by Ekman flow, while island blocking, topographic steering and geostrophic currents also appear to influence current patterns. Tidal amplitudes and phases were unchanged due to SLR of up to 2 m, while maximum current speeds altered by as much as 20 cm/s within some coastal embayments. Non-linear relationships between SLR and maximum current speeds were seen at some coastal reef platform sites. Under higher sea levels, tidal residual currents altered by less than ±2 cm/s which is relatively significant given maximum tidal residual current speeds are typically below 10 cm/s. Our findings indicate that under higher sea levels, coastal processes governing sediment transport, pollutant dispersal and larval transport are likely to alter, which may have implications for coastal environments and ecosystems. Given winds influence coastal circulation and subsequent coastal processes, changes in trade winds due to climate change may act to further alter coastal processes. It is felt that the current modelling approach can be applied to other regions to help fill critical knowledge gaps.